Heat shock protein 90 associates with Toll‐like receptors 7/9 and mediates self‐nucleic acid recognition in SLE. Issue 7 (28th April 2015) - Saito, Keita; Kukita, Kazuharu; Kutomi, Goro; Okuya, Koichi; Asanuma, Hiroko; Tabeya, Tetsuya; Naishiro, Yasuka; Yamamoto, Motohisa; Takahashi, Hiroki; Torigoe, Toshihiko; Nakai, Akira; Shinomura, Yasuhisa; et al.
<x xml:space="preserve">Abstract</x> Systemic lupus erythematosus (SLE) is a prototype systemic autoimmune disease, and disease activity is associated with serum IFN‐α level. Plasmacytoid dendritic cells (pDCs) sense microbial as well as self‐nucleic acids by TLRs 7 and 9 and produce a large amount of IFN‐α. Here, we show that heat shock protein 90 (Hsp90) associates with and delivers TLR7/9 from the ER to early endosomes for ligand recognition. Inhibition of Hsp90 by various approaches including the use of Hsp90 inhibitor, a geldanamycin derivative, suppressed the Hsp90 association with TLR7/9, which resulted in inhibition of IFN‐α production, leading to improvement of SLE symptoms in mice. Notably, we observed that serum Hsp90 is clearly increased in patients with active SLE compared with that in patients with inactive disease. Furthermore, we demonstrated that serum Hsp90 detected in SLE patients binds to self‐DNA and/or anti‐DNA Ab, thus leading to stimulation of pDCs to produce IFN‐α. Our data demonstrate that Hsp90 plays a crucial role in the pathogenesis of SLE and that an Hsp90 inhibitor will therefore provide a new therapeutic approach to SLE and other nucleic acid‐related autoimmune diseases.